1998
DOI: 10.4141/a97-071
|View full text |Cite
|
Sign up to set email alerts
|

Eating quality of beef from animals fed wet brewers' grains and wheat-based wet distillers' grains

Abstract: . 1998. Eating quality of beef from animals fed wet brewers' grains and wheat-based wet distillers' grains. Can. J. Anim. Sci. 78: [143][144][145][146]. The eating quality of beef from steers fed either conventional, brewers' grain or wheat-based distillers' grain rations during backgrounding and finishing was assessed. Carcass traits, raw proximate composition and fatty acid composition of the longissimus muscle were generally unaffected (P < 0.05) by dietary treatment. Furthermore, diet had no effect on sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 7 publications
(15 reference statements)
4
20
0
Order By: Relevance
“…Although analyses were conducted on the musculus longissimus lumborum, Shand et al (1998) reported that cattle finished on wheat-based distillers grains had similar moisture and pH values as reported here, but percentage fat values reported here were approximately 24% greater, which could be due to the source of distillers grains (corn vs. wheat) or muscle differences. Mills et al (1992) reported no statistical differences of i.m.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Although analyses were conducted on the musculus longissimus lumborum, Shand et al (1998) reported that cattle finished on wheat-based distillers grains had similar moisture and pH values as reported here, but percentage fat values reported here were approximately 24% greater, which could be due to the source of distillers grains (corn vs. wheat) or muscle differences. Mills et al (1992) reported no statistical differences of i.m.…”
Section: Discussionmentioning
confidence: 41%
“…Shand et al (1998) reported that cattle finished on wheat-based distillers grains or brewers grain were statistically similar to cattle finished on barley in regards to moisture, fat, pH, cooking losses, and sensory analysis. Likewise, Roeber et al (2005) reported that finishing cattle on dried distillers grains had no effect on sensory attributes of strip loins.…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, however, increases in PUFA were relatively modest; thus they would not be expected to have significantly altered the shelf life or flavor of the meat harvested from these lambs. Shand et al (1998) found that including 14.4% wet wheat-based distillers' grains in a diet for beef cattle did not affect tenderness, juiciness or flavor of beef. Subjective retail display properties of steaks over a 6-d period were also unaffected when cattle were fed 15% corn-or sorghum-based distillers' grains in place of steam-flaked corn (Gill et al 2008).…”
Section: Fatty Acid Compositionmentioning
confidence: 93%
“…Given that the PUFA concentrations were unaltered in this study, they would not be expected to affect the shelf life or flavor of the meat harvested from these lambs. Shand et al (1998) and Jenschke et al (2007) fed 14.4% wet wheat distillers' grain, or up to 50% wet corn distillers' grains in the diet of beef cattle, respectively, and found no diet effects on tenderness, juiciness, or flavor of the meat. The higher concentration of 17:0 in subcutaneous tissue for lambs fed CDDGS is also indicative of a higher energy diet .…”
Section: Fatty Acid Compositionmentioning
confidence: 97%